Syntax-Semantics Interface in Malay Comparatives - Bakar, Norsofiah Abu; Yusoff, Radiah (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Malay is an SVO agglutinative language. The language expresses comparatives morphologically and syntactically. Syntactically, the degree adverb, such as ‘sangat’ and ‘paling’, is used to indicate comparative by placing itu before or after an adjective as shown in (1) to (3): (1) Shafiq seorang ketua yang sangat tegas. (2) Tapi, aku malu pada diri aku sendiri dan malu sangat pada dia. (3) Maka dengan ugama kita Islam inilah senjata kita yang paling tajam dan kuat buat mengalahkan sekalian musuh-musuh kita itu.